Genotoxicity Studies of Titanium Dioxide Nanoparticles (TiO2NPs) in the Brain of Mice - Hanan R. H. Mohamed; Nahed A. Hussien (Scientifica)
Titanium dioxide nanoparticles (TiO2NPs) are excessively used and represent one of the top five most commonly used nanoparticles worldwide. Recently, various studies referred to their toxic potential on various organs using different treatment route. Male Swiss Webster mice were orally administrated TiO2NPs (500 mg/kg b.w.) daily for five consecutive days and then animals were sacrificed at 24 h, 7 days, or 14 days after the last treatment. The present results report that exposure to TiO2NPs produces mild to moderate changes in the cytoarchitecture of brain tissue in a time dependent manner. Moreover, Comet assay revealed the apoptotic DNA fragmentation, while PCR-SSCP pattern and direct sequencing showed point mutation of Presenilin 1 gene at exon 5, gene linked to inherited forms of the Alzheimer’s disease. Therefore, from these findings, the present study concluded that TiO2NPs is genotoxic and mutagenic to brain tissue which in turn might lead to Alzheimer’s disease incidence.